The Philosophy of Human Rights : Contemporary Controversies - Heilinger, Jan-Christoph (2011)
The notion of "human rights" is widely used in political and moral debates. The core idea, that all human beings have some inalienable basic rights, is appealing and has an important practical function: It allows moral criticism of various wrongs and calls for action in order to prevent them. The articles in this collection take up a tension between the wide political use of human rights claims and some intellectual skepticism about them. In particular, three major issues call for clarification: the questions of how to justify human rights, how to determine their scope and the corresponding obligations, and how to overcome the tension between universal normative claims and particular moralities...